“The Right Way at the Right Time”: Insights on the Uptake of Falls Prevention Strategies from People with Dementia and Their Caregivers - Meyer, Claudia; Dow, Briony; Hill, Keith D.; Tinney, Jean; Hill, Sophie (Frontiers in Public Health, 2016)
Strong evidence exists for effective falls prevention strategies for community-dwelling older people. Understanding the translation of these strategies into practice for people with dementia has had limited research focus. People with dementia desire to have their voice heard, to engage meaningfully in the healthcare decision-making process, making it a priority for researchers and practitioners to better understand how to engage them in this process. This paper reports on the qualitative aspects of a series of studies; which aimed to identify the views of people with dementia and their caregivers regarding perceptions of falls prevention and the successes and challenges of adopting falls prevention strategies. Twenty five people with dementia and their caregivers were interviewed in their homes at baseline, and 24 caregivers and 16 people with dementia were interviewed at completion of a 6-month individualised falls prevention intervention. Interviews were audio-recorded, transcribed verbatim and thematically analysed. Five themes were identified at baseline: perceptions of falls; caregivers navigating the new and the unpredictable; recognition of decline; health services – the need for an appropriate message; and negotiating respectful relationships. At six months, caregivers and people with dementia decided on ‘what we need to know’ with firm views that the information regarding falls risk reduction needed to be in ‘the right way…at the right time’. Rather than caregivers and people with dementia being only recipients of knowledge, they felt they were ‘more than just empty vessels to be filled’ drawing on a ‘variety of resources’ within their circle of influence to be able to positively ‘adapt to change’. The voices of people with dementia and their caregivers add an important dimension to understanding the translation of falls prevention knowledge for this population. Insights from this study will enable community care health professionals to understand that people with dementia and their caregivers can, and wish to, contribute to implementing falls prevention strategies through their resourcefulness and inclusion in the therapeutic partnership.